INFLUENCE OF SERVICE QUALITY ON THE SATIFACTION OF PT.PIM COOPERATIVE MEMBERS - Sabina , Dila; dwi winata, Vina; Azizah , Nurul; amanda, Yusra; Anwar, Khairil (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Service quality is a measure of service success which is determined by level service recipient saticfaction. While the level of satisfaction of the recipient of this service will be obtained if a recipient of the service gets the appropriate type of service with what they want and need. While customer satisfaction is the level a person’s feelings after comparing the performance or results, he feels compared with his hopes. This study studies the effect of service quality on satisfaction of members of the PT. PIM syariah employee cooperative. Using the elements of service quality namely RATER (responsiveness, assurance, tangible, empathy, and reliability) from the result of the study has been investigated in the cooperative produces a fairly good level of service to the members of the cooperative, this was disclosed by the staff at the cooperative office on our in- depth interview some time ago.